Aristotle and distributed language: capacity, matter, structure, and languaging. (January 2016) - Lassiter, Charles
Abstract: Non-representational views of language require non-Cartesian concepts. Some in this vein have looked to philosophers such as Husserl, Merleau-Ponty, and Peirce, but none so far have looked to Aristotle. This paper argues that Aristotle's metaphysics offers an attractive and powerful set of concepts to scaffold the distributed language approach. I provide a brief exposition of the central commitments of Aristotelian metaphysics and of the distributed approach to language. After drawing connections between these two sets of concepts, I offer two advantages of this synthesis. First, it allows for a natural incorporation of causal pluralism, which acknowledges that events at different timescales are causally efficacious in different ways. Second, it enables reinterpretation of findings from orthodox linguistics; insights about the structure of language are preserved but the ontological commitments to internal representations are abandoned. Highlights: Provides an overview of the distributed language approach to the language sciences. Introduces Aristotelian concepts relevant to distributed language. Synthesizes Aristotelian and distributed language conceptual frameworks. Applies synthesis to a case-study that employs the distributed language approach. Offers suggestions for future work.